Effect of Heparin and Heparin Fractions on Platelet Aggregation - Salzman, Edwin W. (1980)
Porcine intestinal mucosal heparin induced aggregation of platelets in citrated platelet-rich plasma and enhanced platelet aggregation and serotonin secretion induced by other agents. This action of heparin was blocked by substances that elevate platelet cyclic AMP and by EDTA but not by inhibitors of platelet cyclooxygenase. The effect was not inhibited by apyrase or by N-amylthio-5′-AMP and therefore did not require the action of ADP, nor was there activation of platelet phospholipase. Platelet aggregation by heparin required a plasma cofactor different from the cofactor required for ristocetin. Fractionation of heparin yielded preparations that varied in molecular weight and, within a given molecular weight fraction, in affinity for antithrombin III. Fractions of high molecular weight (average 20,000) were more reactive with platelets than were fractions of low molecular weight (7,000). Anticoagulant activity did not parallel the platelet reactivity of heparin fractions. Among high molecular weight fractions, preparations of high or low antithrombin affinity were equally active in induction of platelet aggregation. In low molecular weight fractions, there was an inverse relationship between platelet reactivity and anticoagulant activity in normal platelet-rich plasma, but, in platelet-rich plasma depleted of antithrombin, low molecular weight fractions of high and low antithrombin affinity reacted equally with platelets. These results suggest that formation of an antithrombin-heparin complex protected platelets from aggregation by heparin. Selection of heparin fractions of low molecular weight and high antithrombin affinity may improve anticoagulant therapy and development of thromboresistant heparin-coated artificial materials.